2018
DOI: 10.1038/s41598-018-28314-z
|View full text |Cite
|
Sign up to set email alerts
|

Preventive treatment with liraglutide protects against development of glucose intolerance in a rat model of Wolfram syndrome

Abstract: Wolfram syndrome (WS) is a rare autosomal recessive disorder caused by mutations in the WFS1 (Wolframin1) gene. The syndrome first manifests as diabetes mellitus, followed by optic nerve atrophy, deafness, and neurodegeneration. The underlying mechanism is believed to be a dysregulation of endoplasmic reticulum (ER) stress response, which ultimately leads to cellular death. Treatment with glucagon-like peptide-1 (GLP-1) receptor agonists has been shown to normalize ER stress response in several in vitro and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 42 publications
11
46
0
Order By: Relevance
“…The Wfs1 KO rats were already glucose intolerant at the beginning of the experiment (Fig. 1a,b) (F(1, 30) = 38.69, p < 0.001 (genotype)), which agrees with our previous studies 6,8 . As expected, 13-month-old KO animals were still glucose intolerant (Fig.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The Wfs1 KO rats were already glucose intolerant at the beginning of the experiment (Fig. 1a,b) (F(1, 30) = 38.69, p < 0.001 (genotype)), which agrees with our previous studies 6,8 . As expected, 13-month-old KO animals were still glucose intolerant (Fig.…”
Section: Resultssupporting
confidence: 91%
“…For that reason, it is important to find not only antidiabetic treatments but also therapies that could delay the progression of neurodegeneration and thereby extend the quality of life and lifespan of WS patients. We have shown that the GLP-1 receptor agonist liraglutide has the ability to slow down the progression of the diabetic phenotype in our validated Wfs1-deficient rat model 8 . Wfs1 and GLP-1 receptor are both expressed in the inferior olive and in the retina, and therefore treatment with the GLP-1 receptor agonist may have a direct neuroprotective effect on those structures 6,1214 .…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Mutations in WFS1 , the wolframin gene, are responsible for the development of Wolfram syndrome, an autosomal recessive disease characterized by a variety of disorders including diabetes mellitus [ 167 ]. In a mice study researchers have demonstrated that treatment with GLP1RA may improve beta cell function, show a neuroprotective effect and even preserve from glucose intolerance in case of preventive therapy [ 168 , 169 , 170 , 171 ]. As GLP1RA may be considered as a potential therapy for wolfram syndrome treatment, analysis of association between WFS1 gene polymorphism and GLP1RA efficacy becomes reasonable.…”
Section: Genes Associated With Dpp4-inhibitors and Glp1 Receptor Amentioning
confidence: 99%
“…Treatment tests do not actually require expertise in pathogenesis, although it certainly helps. Treatments for Niemann-Pick C1 (Fan et al, 2013), Wilson's disease (Muller et al, 2018), Wolfram's disease (Toots et al, 2018), cyclin-dependent kinase-like 5 deficiency disorder (Yennawar et al, 2019), and many others have been tested. However, in these studies systems biology methods are infrequently used and the treatment efficacy is judged by symptomatic relief or individual biomarkers.…”
Section: Figmentioning
confidence: 99%